(3cJGH GdSehes
(3ChdgG (B:s
(3Chd GdehLhO ajg bhdg MJi JRhd Yfg GdCYQGV aEPG RGdJ Yfg abW Sde s
(3BNQgG (B:s
(3ajNdW HMH GdUfhHQ hgh cGdYdc jNdWG HShGA hGSMbgeG LejYkG hGVQHgeG HOgf GdNjQi abO GcedfG eG hLOfG Cf fPcQg hTQMfGg eG bOQfG Ydjg ef GdSehe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3LRA efg hdjS GdeNWhW cdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs